Die Chronologie der Kuretenstraße: Archäologische Evidenzen zur Baugeschichte des unteren Embolos von Ephesos von der lysimachischen Neugründung bis in die byzantinische Zeit. - Waldner, Alice (2020)
The contextual analysis of find contexts from the excavations that were conducted in the area of the lower Embolos (Curetes Street) resulted in a new understanding of about one thousand years of use (3rd century BCE - 7th century CE). They relate to the design and the route of the street, the building history of the construction along its edge and its varied function.